PISABUJI BALOG PADA E-JURNAL M3 BERPRINSIP UTAMI UNTUK MENINGKATKAN PRODUK INOVATIF KEANEKARAGAMAN HAYATI BERBASIS STEAM - Utaminingsih, S.Si, M.Pd, Sri (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2021)
This study aims to (1) describe E-Journal M3(Membaca, Menulis, Menalar) with the UTAMI principle (Reading and Writing Every Day); (2) explore the application of PISABUJI ​​BALOG (Pikir, Desain, Buat, Uji, Lombakan, Buat Vlog) by utilizing E-Journal M3with the UTAMI principle to create STEAM-based innovative biodiversity products; and (3) identify aspects of STEAM contained in innovative biodiversity products produced by students. This research is a best practice by involving the students of class X IPA 1 of SMAN 1 Ponggok as the research subjects. The data were obtained by using observation sheets and assessment sheets. The stages of this research include brainstorming, introduction of basic competencies and indicators, tasks presentation, group formation, screening of the best Vlog created by seniors, and application of PISABUJI ​​BALOG. This process utilizesE-Journal M3 with the UTAMI principleboth for the product creation and product dissemination. The results showed that the students' literacy increased significantly from 0.1 to 3.0 on average. The students are able to create STEAM-based innovative products with an average score above the KKM, which ranges from 88 to 91.8. The students’ innovative products are original, unique, and have the selling point. The student-made products and Vlogs contain elements of STEAM that correspond tothe 21st century skills.